GAMBARAN PENDAPAT KELUARGA ODGJ (ORANG DENGAN GANGGUAN JIWA) TENTANG PENYEBAB TERJADINYA GANGGUAN JIWA DAN PENGOBATANNYA PADA MASYARAKAT MELAYU DI KABUPATEN KEPULAUAN MERANTI - wati, Megawati (Universitas Aufa Royhan, 2022)
ABSTRACT Mental disorders are influenced by two factors that cause namely predisposing factors and precipitation factors. This study aims to describe the opinion of the family of ODGJ (People with Mental Disorders) about the causes of mental disorders and their treatment in the Malay community in the Meranti Islands. this study used a quantitative descriptive design. the results of the univariate analysis of the majority of respondents aged 17-25 years (late teens) (26.7%), the majority of respondents are female (80%), the majority of respondents have high school education (36.7%), the majority of respondents work as household workers (46.7%), genetic predisposing factors the majority of respondents have no family members who have mental disorders (86.7%), the majority of respondents have psychosocial disorders of rejection (28.6%), the majority of respondents have a history of unpleasant past experiences physical violence (23.5%), based on the type of treatment, most of the respondents took informal treatment (63.3%). Keywords: Family Opinion, Causes of Mental Disorders, Seeking Treatment